The Association between eGFR and the Aldosterone-to-Renin Ratio and Its Effect on Screening for Primary Aldosteronism. (7th February 2020) - Xu, Jing; Yang, Yumei; Ling, Yan; Lu, Zhiqiang; Gao, Xin; Li, Xiaomu; Li, Xiaoying
Abstract : Objectives . Long-term exposure to excessive aldosterone secretion from the adrenal gland may cause renal damage in patients with primary aldosteronism (PA). The aldosterone-to-renin ratio (ARR) may be significantly affected by renal function, especially in patients with renal damage related to long-term PA. The objective of this study was to investigate the association between the estimated glomerular filtration rate (eGFR) and ARR as well as its effect on screening for PA. Methods . This study was performed in Zhongshan Hospital, Fudan University, China. 803 patients with hypertension were consecutively recruited from 2012 to 2015. All participants underwent routine biochemical measurements, including plasma renin activity (PRA) and plasma aldosterone concentration (PAC). In all patients with a PAC higher than 10 ng/dl, a saline perfusion test was conducted, and a CT scan or adrenal venous sampling was also performed if needed. Receiver operating characteristic (ROC) analysis was conducted in all eGFR < 90 and eGFR ≥ 90 groups separately to determine the optimal cut-off values of ARR. Results . The optimal cut-off point for PA was an ARR of 40 ng/dl per ng/ml.h in the whole population, 52 ng/dl per ng/ml.h in subjects with an eGFR higher than 90 ml/min/1.73 m 2, and 18 ng/dl per ng/ml.h in subjects with an eGFR lower than 90 ml/min/1.73 m 2 . Patients with an eGFR higher than 90 ml/min/1.73 m 2 had significantly lower PRA and higher ARR levels than patients with an eGFR lower than 90 ml/min/1.73 m 2  (P < 0.05 ). Conclusions . Unsuppressed renin and lower ARR levels were associated with decreased eGFR in patients with primary aldosteronism. Diagnostic criteria of ARR by stratified eGFR may be an optimal strategy for the screening of primary aldosteronism.